2011
DOI: 10.1186/1471-2415-11-18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pseudoexfoliation Syndrome and Pseudoexfoliation Glaucoma in Upper Egypt

Abstract: BackgroundPseudoexfoliation (PXF) is a recognized risk factor for developing cataract, glaucoma and lens dislocation. PXF is also associated with increased risk of complications during cataract surgery due to poor mydriasis and zonular weakness. The aim of this study is to report the prevalence of pseudoexfoliation among Upper Egyptians attending the ophthalmology clinic of Assiut University Hospital.MethodologyA retrospective, chart review study conducted in the period from February 2002 to August 2009. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 28 publications
4
17
4
1
Order By: Relevance
“…The high frequency of glaucoma in this hospital-based study may be due to the regular follow-ups attended by glaucoma patients. Similarly a high frequency of glaucoma has been found in hospital-based studies with reported rates of 33.1% by Al-Bdour et al [17], 30.3% by Shazly et al [23], and 40% by Rao et al [24]. Kaljurand and Teesalu [25] reported a high frequency of 35.7% for glaucoma in their population-based study although the glaucoma frequency is generally lower in population-based studies [4, 26, 27].…”
Section: Discussionsupporting
confidence: 57%
“…The high frequency of glaucoma in this hospital-based study may be due to the regular follow-ups attended by glaucoma patients. Similarly a high frequency of glaucoma has been found in hospital-based studies with reported rates of 33.1% by Al-Bdour et al [17], 30.3% by Shazly et al [23], and 40% by Rao et al [24]. Kaljurand and Teesalu [25] reported a high frequency of 35.7% for glaucoma in their population-based study although the glaucoma frequency is generally lower in population-based studies [4, 26, 27].…”
Section: Discussionsupporting
confidence: 57%
“…However, a hospital-based study in Saudi Arabia and Pakistan found 45% and 40% of patients with PXS to have high IOP [6,9]. Also the prevalence of elevated IOP associated with exfoliation syndrome in this study was lower than has been reported by Al Jaffal Z and Kayyali in Syria (37.5%) [10], Al-Bdour et al in Jordan (33.1%), [11] Shazly et al in Egypt (30.4%) [12] and Yalaz et al in Turkey (32.1%) [13]. In India, 34% of exfoliation syndrome patients have "manifest glaucoma," although the criteria for the diagnosis of glaucoma are not detailed [14].…”
Section: Discussioncontrasting
confidence: 64%
“…The prevalence of PXS in Nigerian communities has been reported to be very low [16]. However; several investigators have reported high proportions of PXG among patients with PXS, ranging from 30.3% [17] to 67% [16].…”
Section: Introductionmentioning
confidence: 99%